Determining the Optimal Capital Structure of PT. Krakatau Steel Tbk (Persero) - Muhammad Rafif Adiguna; Oktofa Yudha Sudrajad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Indonesia's steel industry is expected to keep growing, with the country's steel consumption projected to increase from 17.4 million tons in 2023 to 18.3 million tons in 2024, while production is expected to increase from 15.2 million tons to 15.9 million tons. However, PT Krakatau Steel Tbk, or KRAS, is one of the leading players in this sector, with big challenges ahead that it is facing and thus affecting its performance. One of the critical contributory factors is the increased volumes of steel imports, which heighten competition and have led to a significant decline in revenue. This is because the cheaper steel imports, especially those from countries like China, are contributing to putting pressure on prices and further complicating the market status quo for KRAS. This research study seeks to analyze and determine the optimal capital structure for KRAS with a focus on enhancing its financial stability and overall value. In this research author analyse and explore for the solution with external analysis using PESTLE Analysis. Based on secondary data from annual reports and relevant academic literature, the study evaluates the financial performance of KRAS from 2021 to 2023. The results showed a significant revenue decline of 35.68% from 2022 to 2023, mainly influenced by increased import competition and unstable global steel prices. Beyond this, high leverage remains a concern for KRAS, which has liabilities, even though it declined from $3.16 billion in 2021, having reached $2.35 billion as of 2023.